PENGARUH STORE ATMOSPHERE TERHADAP KEPUASAAN KONSUMEN PADA CAFE REFRESHO DI KOTA PALU - ATIFA, FIRDHA NUR (Fakultas Ekonomi Universitas Tadulako, 2015)
This research aims to determine the influence of store atmosphere on consumer satisfaction at Cafe Refresho in Palu City. The independent variables used in this study are Exterior (X1), General Interior (X2), Store Layout (X3) and Interior Display (X4), while the dependent variable is consumer satisfaction (Y). This type of research is quantitative. The method of this research is descriptive causal. Samples used in this study are 100 respondents and using purposive sampling technique. Data analysis method used in this research is multiple linear regression analysis method. The results of this study indicate that simultaneously Store Atmosphere elements consisting of Exterior, General Interior, Store Layout, and Interior Display have a significant effect on consumer satisfaction at Cafe Refresho in Palu City. Partially Store Atmosphere elements consisting of General Interior, Store Layout, and Interior Display have a significant effect on consumer satisfaction at Cafe Refresho in Palu City. While the Exterior element partially have no significant effect on consumer satisfaction at Cafe Refresho in Palu City.